2020
DOI: 10.1177/0954407020901368
|View full text |Cite
|
Sign up to set email alerts
|

Study on the strength of converted school pick-up truck’s roof in case of rollover accidents

Abstract: In 2015, it has been reported that road traffic fatality rate in Thailand ranks number 2 in the world at 36.2 per 100,000 with an annual estimate of 66 deaths every day. Based on the survey of the Road Safety Group Thailand in 2017, at least one student got injury by school transport each day. A recent survey also revealed that the number of private hire pick-up trucks as school buses in Thailand, especially in upcountry areas, is increasing due to its lower cost in comparison to that of a van or a minibus. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The vehicle defects causing the pre-crash consisted mainly of overloading and modification [32]. The environmental defects pre-event were documented as many fixed objects in the safety zone, no traffic lights, no guard rails, and no traffic signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vehicle defects causing the pre-crash consisted mainly of overloading and modification [32]. The environmental defects pre-event were documented as many fixed objects in the safety zone, no traffic lights, no guard rails, and no traffic signs.…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle safety standards in all vehicles are essential to the safety of drivers and passengers [17][18][19][20]28]. Several studies have found that vehicle qualities affecting accident risk include inadequate maintenance, mismatched tires [20,30,31], compromised braking [20], insufficient lighting, overloading, and the misuse or modification of vehicles for public transportation or as school vehicles [27,32,33]. A lack of safety equipment inside the vehicles contributes to a high risk of serious disability, serious injury, and death [23,26,27].…”
Section: Vehicle Risks Related To Road Traffic Accidents and Road Tra...mentioning
confidence: 99%